1995
DOI: 10.1161/01.res.76.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Vascular Smooth Muscle Cells and the Regulation of Protein Kinase C-α

Abstract: Dedifferentiation and proliferation of vascular smooth muscle cells (VSMCs) are important features of atherosclerosis. The molecular mechanisms are largely unclear; however, protein kinase C (PKC) is a key enzyme in the intracellular signaling pathways that mediate this process. We studied the activity and immunoreactivity of PKC-alpha in primary cultures of VSMCs from rat aortas under different conditions of growth and differentiation. PKC-alpha was determined under the following conditions: (1) during the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 39 publications
3
75
1
Order By: Relevance
“…This observation could indicate that VEGF induces a translocation of PKC-␣ into the nucleus. Nuclear translocation of this isoform by tyrosine kinase receptor signaling has been reported previously by us 21,30,31 and others. [32][33][34] Which signal directs PKC isoforms to the nucleus is presently unclear.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This observation could indicate that VEGF induces a translocation of PKC-␣ into the nucleus. Nuclear translocation of this isoform by tyrosine kinase receptor signaling has been reported previously by us 21,30,31 and others. [32][33][34] Which signal directs PKC isoforms to the nucleus is presently unclear.…”
Section: Discussionsupporting
confidence: 68%
“…37 We recently showed that retinoic acid-induced differentiation of vascular smooth muscle cells is associated with increased expression of PKC-␣ and that this isoform can induce differentiation in these cells. 30 Others have suggested that PKC-␣ may be among the most likely mediators of G1/S inhibition in endothelial cells. 38 -40 VEGF also induced a translocation of PKC-, and the confocal micrographs show an increased immunoreactivity in the cytosol and in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PKCb was not detected in either freshly isolated or proliferating smooth muscle cells. In another study, PKCa was downregulated when rat vascular smooth muscle cells assumed a proliferative/secretory phenotype [117]. When the cells reassumed their contractile state, PKCa expression reverted to normal levels.…”
Section: Expression and Function Of Protein Kinase C Isoforms In Prolmentioning
confidence: 93%
“…The actin content of cultured smooth muscle cells decreases when the cells change shape and move (Haller et al 1995). Actin assembly is partly controlled by extracellular signals such as stretch, adhesion to the extracellular matrix and growth factors, many of which are sequestered in the matrix (Wilson et al 1995 ;ChrzanowskaWodnicka & Burridge, 1996 ;Dinbergs et al 1996 ;O'Reilly et al 1997).…”
Section: mentioning
confidence: 99%